2020
DOI: 10.1177/1350650120954949
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behaviour of natural fibre 3D braided woven fabric reinforced PLA composites

Abstract: This study aims to investigate the potential of natural fibre 3D braided woven fabric (NFBF) reinforced PLA (poly lactic acid) composites for tribological applications. Composites with different fibre contents are prepared using film stacking process and hot press methods. Friction co-efficient and wear rate of the composites are analysed using pin-on-disc tribometer under dry contact sliding condition and various operating conditions (velocity and load) for a fixed sliding distance of 3000 m. The morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Moreover a gradual increase in volumetric wear was observed with increase in sliding distance, sliding velocity and normal load. Similar results for wear rate were reported by others [42][43][44] for PLA composites where wear rate was found to increase with increased normal load. Moreover, authors reported that wear behavior of the manufactured PLA composites was remained more sensitive to load variation than the sliding velocity variations.…”
Section: Sliding Wear Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover a gradual increase in volumetric wear was observed with increase in sliding distance, sliding velocity and normal load. Similar results for wear rate were reported by others [42][43][44] for PLA composites where wear rate was found to increase with increased normal load. Moreover, authors reported that wear behavior of the manufactured PLA composites was remained more sensitive to load variation than the sliding velocity variations.…”
Section: Sliding Wear Analysissupporting
confidence: 90%
“…The worn surface of neat PLA (Fig. 7a) sliding for 400 m distance at 10 N load and 1 m/s velocity [test run 1 within Table S1 (supplementary materials)] was characterized by smooth surface, along with small grooves due to micro-ploughing and peeling-off matrix material was also observed, all suggesting mild wear [43,47,48]. With the inclusion of MD (5-15 wt%, Fig.…”
Section: Sliding Wear Analysismentioning
confidence: 99%
“…Rather than having disadvantages such as low modulus of elasticity, high moisture absorption, and decomposition in the biological assault, the most significant characteristic of green composites is their complete biodegradability with no negative environmental impact [ 11 , 12 ]. Further feasibility research into the possible use of natural fibers as reinforcing compounding materials for use in many applications is also generating many economic and environmental impacts [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The current study examines recent research and developments in PLA-based green composites and their mechanical properties in terms of tensile strength, compressive strength, flexural properties, and impact strength, as well as some of the fundamental issues in the construction of such composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in the case of the unfilled polymer, the coefficient of friction fluctuates during the remaining part of the test. Interestingly, the steady state is typically not achieved in published studies on the tribological properties of polylactide-based materials [ 46 ]. For example, in the case of 3D-printed PLA, fluctuation of the coefficient of friction was explained by elastic recovery of the material [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of them are still embedded in the polymeric material, but debonding of the linseed cake particles also occurs. This behavior results from limited adhesion of the hydrophilic plant-based filler and hydrophobic polymer and commonly occurs in the case of polymeric composites filled with natural substances [ 46 ]. Interestingly, the number of visible filler particles and debonding sites decreases along with the oil content in linseed cake.…”
Section: Resultsmentioning
confidence: 99%